Pathology Slide Review in Vulvar Cancer Does Not Change Patient Management. (25th March 2014) - Beugeling, Maaike; Ewing-Graham, Patricia C.; Mzallassi, Zineb; van Doorn, Helena C.
Abstract : Hypothesis . Pathology slide review in vulvar cancer is only necessary in a restricted number of cases. Methods . A retrospective chart review of all cases of vulvar cancer treated in a tertiary centre between January 1, 2000, and April 1, 2006. Histopathology reports from the referring and tertiary centre were compared. Results . 121 pathology reports from 112 patients were reviewed. Of the original reports, 56% were deemed adequate, commenting on tumor type and depth of infiltration; of the reviews, 83% were adequate. Conclusion . There were no discrepancies that influenced patient management. We suggest that vulvar cancer biopsies need to be reviewed only when the tumor is less than 10 mm in linear extension, when the infiltration is 1 mm or less, when there is no residual tumor on inspection, and in any nonsquamous cancer.